2004
DOI: 10.1081/ppt-120038054
|View full text |Cite
|
Sign up to set email alerts
|

New Economical Filler for Elastomer Composites

Abstract: Incorporation of fillers in elastomers results in a profound effect on mechanical properties of the composites formed. Significant study has been carried out on this topic. Fillers are customarily classified into organic and inorganic. The latter class includes calcium carbonate, talc, barium sulphate, china clay (kaolin), magnesium oxide, alumina, silica, etc. Flyash, a waste product of thermal power stations contains inorganic oxides, hence, it was thought that it could be used as filler for elastomers. Flya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…9,No.3 also shown the advantageous use of treated fly ash in a wide variety of polymer matrices. [4][5][6][7][8] Although incidental success stories are published, a systematic approach on investigating the influence of fly ash on polymer properties for the various different polymer types and the enormous amount of possible formulations has not yet been properly undertaken. As a part of an attempt into this direction, the present work deals with HDPE-fly ash composites.…”
Section: Introductionmentioning
confidence: 99%
“…9,No.3 also shown the advantageous use of treated fly ash in a wide variety of polymer matrices. [4][5][6][7][8] Although incidental success stories are published, a systematic approach on investigating the influence of fly ash on polymer properties for the various different polymer types and the enormous amount of possible formulations has not yet been properly undertaken. As a part of an attempt into this direction, the present work deals with HDPE-fly ash composites.…”
Section: Introductionmentioning
confidence: 99%
“…The "d" values and relative intensities I/I o of X-ray pattern for samples of prepared pigments were illustrated in Figure 1, and the data showed that for the three mixtures including 3Al 2 …”
Section: X-ray Diffraction Of Different Samples Of Ironaluminum Oxidementioning
confidence: 99%
“…2 It was found that the Einstein-Guth-Gold equation could be applied to the filled vulcanizates over a wide range of strains if the effective volume of the filler was introduced.…”
Section: Effect Of the Investigated Fillers On The Physicomechanical mentioning
confidence: 99%
See 2 more Smart Citations